Calibration and Validation of Swarm Plasma Densities and Electron Temperatures Using Ground‐Based Radars and Satellite Radio Occultation Measurements. Issue 1 (9th January 2018) - Lomidze, Levan; Knudsen, David J.; Burchill, Johnathan; Kouznetsov, Alexei; Buchert, Stephan C.
Abstract: In this study we calibrate and validate in situ ionospheric electron density ( N e ) and temperature ( T e ) measured with Langmuir probes (LPs) on the three Swarm satellites orbiting the Earth in circular, nearly polar orbits at ~500 km altitude. We assess the accuracy and reliability of the LP data (December 2013 to June 2016) by using nearly coincident measurements from low‐ and middle‐latitude incoherent scatter radars (ISRs), low‐latitude ionosondes, and Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) satellites, covering all latitudes. The comparison results for plasma frequency ( f ∝ N e ) for each Swarm satellite are consistent across these three, principally different measurement techniques. It shows that the Swarm LPs systematically underestimate plasma frequency by about 10% (0.5–0.6 MHz). The correlation coefficients are high (≥0.97), indicating accurate relative variation in the Swarm LP densities. The comparison of T e from high‐gain LPs and those from ISRs reveals that all three satellites overestimate it by 300–400 K but exhibit high correlations (0.92–0.97) against the validation data. The low‐gain LP T e data show larger overestimation (~700 K) and lower correlation (0.86–0.90). The adjustment of the Swarm LP data based on Swarm‐ISR comparison results removes the systematic biases in the Swarm data and gives plasma frequencies and high‐ and low‐gain electron temperatures that are precise within about 0.4 MHz (8%), 150–230 K, and 260–360 K, respectively. We demonstrate that the applied correction significantly improves the agreement between (1) the plasma densities from Swarm, and from ionosondes and COSMIC, and (2) the T e from Swarm LPs and International Reference Ionosphere 2016. Key Points: Swarm Langmuir Probe (LP) data are compared to independent ground‐ and space‐based measurements Initial Swarm LP data show systematic errors but high correlations with data from other techniques Adjustments based on incoherent scatter radar data significantly improve the accuracy of LP data